Globalisation and the Anthropocene: The Reconfiguration of Science Education for a Sustainable Future - Donald Gray; Laura Colucci-Gray (Universidade de Lisboa, 2014)
In this article we discuss current impacts on the planet as a result of technoscientificdevelopments and neo-liberal policy. We argue that science educationhas an important role to play in supporting society to respond to newchallenges ahead. However there needs to be a change to the way in whichscience is introduced in schools to raise awareness of complex global interconnectednessand our embeddedness in the natural (and increasingly altered)planetary cycles. Such awareness changes how we view the practiceof science and the way in which science is presented in schools. Drawing onrecent literature, this paper will present an argument for the reconfigurationof science education for a sustainable future.